La ética del mundo en que vivimos - Joan Fontrodona (Estudios sobre Educación, 2018)
Ethics in the global society can serve as a reference point so as not to loose our way in this changing and uncertain world. A series of ethical parameters are suggested to facilitate the proactive nature of each person in his/her relations with the world.